The neural, cognitive and behavioural mechanisms of EGM play - Shao, R (2012)
BACKGROUND: Electronic Gaming Machine (EGM) play may be particularly addictive. However, we know little about the relationships between near-misses, illusions of control, impulsivity and people's attitudes and behaviours towards the game, as well as changes in neural systems as people acquire more experience with EGM play. METHODS: Experiment 1 used the indirect Functional Magnetic Resonance Image (fMRI) technique to examine the neural signals of dopaminergic reinforcement circuitries evoked by playing a simple slot-machine among practiced participants who had previous game experience and unpracticed participants who had no such experience. Experiment 2 examined the influence of impulsivity and illusions of control on Blood Oxygen Level Dependent (BOLD) signals elicited by slot-machine outcomes. Experiment 3-5 investigated the effect of near-miss frequency on people's valuations of slot-machine games, indicated mainly by purchasing of optional plays, when co-occurring with different frequencies of wins. We also tested how the interactive influence of near-miss and winning frequencies on game valuations was associated with gambling-related cognitive biases. Experiment 3-5 also tested a novel card-guessing game designed to provide valid behavioural measure of illusions of control. RESULTS: Prior slot-machine experience was associated with shift of dopaminergic signals in the ventral striatum from the rewarding outcomes to the reel-spins. Impulsivity enhanced dopaminergic responses to wins but suppressed signals to near-misses. Illusions of control potentiated neural signals to near-misses in the practiced participants. Winning slot-machine outcomes exerted principle influence on game valuations, whereas the effect of near-misses was weak. However, some evidence indicated that the influence of near-miss frequency on game valuations depended on the frequency of wins. Individuals holding more positive gambling expectancies showed buying behaviours that were under less positive interactive influence of winning and near-miss frequencies. Our card-guessing game was successful in eliciting behavioural patterns indicative of illusions of control. CONCLUSIONS: A dopaminergic neural mechanism is implicated in the acquisition of slot-machine experience. Near-misses may not simply act as 'mini-wins'. The effect of near-misses on game valuation is subtle and may depend on the frequency of co-occurring wins.